Human defensins and Th-1 cytokines in hepatitis C viral infection - Owusu, Dorcas Ohui; Owusu, Michael; Owusu, Bright Afriyie (Pan African Medical Journal, 2024)
This is an article published by Dorcas Ohui Owusu et al. Human defensins and Th-1 cytokines in hepatitis C viral infection. Pan African Medical Journal. 2020;37(103). 10.11604/pamj.2020.37.103.25211 Available online at: https://www.panafrican-med-journal.com//content/article/37/103/full